Quantitation of small molecules from liquid chromatography-mass spectrometric accurate mass datasets using CycloBranch - Novák, Jiří; Schug, Kevin A; Havlíček, Vladimír (European journal of mass spectrometry (Chichester, England), 2023)
Gaussian and exponentially modified Gaussian functions were incorporated into integrating algorithms used by an open-source, cross-platform tool called CycloBranch. The quantitation is demonstrated on bacterial pyoverdines separated by fine isotope features. Using our algorithm, we can separate the m/z values 694.25802 and 694.26731 (a 0.009 Da difference), where the former belongs to the most intense peak of pyoverdine D (PvdD), and the latter to the second most intense peak of pyoverdine E (PvdE) in the respective isotopic clusters of [M + Fe-H]2+ ions. The areas under chromatographic curves of standards were analyzed for the limit of detection (LOD), limit of quantitation (LOQ), and regression coefficient calculations. The quantitative module returned a LOD and LOQ of 1.4 and 4.3 ng/mL, respectively, for both PvdD and PvdE in human urine. If present and detected in mass spectra, the intensities of user-defined [M + H]+, [M + Na]+, [M + K]+, [M + Fe-H]2+, or other ion types, can be accumulated and used for quantitation. The quantitation result is returned by CycloBranch in seconds or minutes, contrary to an hours-long manual approach, prone to user-born errors originating from necessary copying among various software environments. Native Bruker, Waters, Thermo, txt, mgf, mzML, and mzXML data formats are supported in CycloBranch, which is freely available at https://ms.biomed.cas.cz/cyclobranch.
Keywords: algoritmy; Software; software; Chromatography, Liquid; Isotopes; mass spectrometry; Humans; chromatografie kapalinová; lidé; Algorithms; hmotnostní spektrometrie; annotation; high resolution; Siderophores; izotopy; dereplication; Mass Spectrometry; quantitation